Digitalization of Education and Its Impact on Urban Society: A Study on Junior High School Teachers - Aas Siti Sholichah; Mufasir Alam; Dendi Dendi; EE. Junaedi Sastradiharja (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the impact of digitalization of education on urban society. The Background of this research is that the rapid development of technology and information has resulted in changes in various aspects of life, especially in urban areas. One area that feels the impact is the realm of education. The teacher’s ability to provide material accompanied by suitable methods will provide good learning outcomes. The approach in this research is qualitative by using an evaluation method through case studies. This is done by two junior high schools in the Jabodetabek region. The impact of digitalization of education for urban communities is the opening of understanding of teachers and students about the benefits of digital in the world of education. It started the program by making every student aware of the importance of reading through the School Literacy Movement by facilitating students and teachers with libraries. Education is developing in the digitalization of education by encouraging students and teachers to use digital libraries. This effort is strengthened by implementing learning by making digital-based teaching materials, namely by including images, photos and videos in each lesson. One of the teacher's innovations in digital-based learning is to facilitate virtual field trips, where each student can access various interesting information and historical places by using the services of a bolger or guide directly at the destination.